Ten genes and two topologies: an exploration of higher relationships in skipper butterflies (Hesperiidae) - Sahoo RK; Warren AD; Wahlberg N; Brower AVZ; Lukhtanov VA; Kodandaramaiah U (PEERJ INC, 2022)
Despite multiple attempts to infer the higher-level phylogenetic relationships of skipper butterflies (Family Hesperiidae), uncertainties in the deep clade relationships persist. The most recent phylogenetic analysis included fewer than 30% of known genera and data from three gene markers. Here we reconstruct the higher-level relationships with a rich sampling of ten nuclear and mitochondrial markers (7,726 bp) from 270 genera and find two distinct but equally plausible topologies among subfamilies at the base of the tree. In one set of analyses, the nuclear markers suggest two contrasting topologies, one of which is supported by the mitochondrial dataset. However, another set of analyses suggests mito-nuclear conflict as the reason for topological incongruence. Neither topology is strongly supported, and we conclude that there is insufficient phylogenetic evidence in the molecular dataset to resolve these relationships. Nevertheless, taking morphological characters into consideration, we suggest that one of the topologies is more likely.